Pathological and clinical findings in a series of 67 cases of medullary carcinoma of the thyroid. Issue 2 (March 1966) - Williams, E. D.; Brown, C. L.; Doniach, I.
Abstract : The pathological features of 67 cases of medullary carcinoma of the thyroid were studied, and when possible the case histories were reviewed. The typical tumour is sharply demarcated but not encapsulated, is composed of sheets of cells having eosinophilic granular cytoplasm, with the deposition of amyloid in the stroma. We would stress the frequency of binucleate cells, the scarcity of mitoses, and the frequent occurrence of calcification. The clinical findings show a wide variation in age at presentation of this tumour, and a wide variation in prognosis, with a mean survival from the time of presentation to hospital of 6·6 years, the longest being 21 years. Two of this group of patients also had phaeochromocytomas; these two and three others showed small papillary tumours of the eyelids, lips, and tongue. Despite the variation in some of its characteristics, medullary carcinoma of the thyroid is considered to be a distinct and sharply defined entity. It appears to be the only type of thyroid carcinoma associated with phaeochromocytoma, the only type associated with multiple mucosal neuromas and the only type with a familial incidence. These findings emphasize the validity of its separation from other types of thyroid carcinoma.